Nutritional status among children aged 6-59 months in flood affected and non-affected areas in Saptari district of Nepal. - Chaudhary, Asha (2019)
Summary: Nutrition well being is an essential of fastest achievement of Sustainable Development Goals (SDG). Child under nutrition is still remains as a major risk factor which drives most deaths, diseases and disability globally. Flood has serious impact on crops productivity and human health in the past. The flood during 10-13 August 2017 in Nepal has induced severe impacts on the basic needs of human beings. Children of aged 6-59 months are most vulnerable to disaster, food insecurity, hygiene and sanitation and then malnutrition. So, the purpose of this study was to access the nutritional status of flood affected and non-affected children of aged 6-59 months along with the effect of flooding on under nutrition indicators. The study was community-based comparative cross-sectional conduced in Saptari district of Neal including total sample size of 372 (186 flooded and 186 non-flooded) after 14 months of Terai flood of 2017 in Saptari. Cluster sampling followed by probability proportionate to their size (PPS) method was used to select cluster and children were randomly selected. A structured questionnaire was used through face to face interview. For anthropometric measurements, Seca digital weighing scale, height board of UNICEF and MUAC tape were used and bilateral pitting edema was also checked. Ethical principles were considered and applied during research. Data were entered into Epi-data version 3.1 than exported to SPSS version 16.0 for analysis. Anthropometric calculation was carried out using ENA for SMART software and nutritional status was assessed using WHO standard. Cross tab and Independent sample t-test was done for descriptive purpose. The association between various under nutrition indicators, flooding and some other factors were assessed by using bivariate and multivariate logistic regression. Prevalence of wasting was 33.5 % (with five cases of edema) in flooded and 21.6% (with one case of edema) in non-flooded cohort. Majority of children of age group 617 months were severely wasted; 14.6% in flooded and 6.7% in non-flooded cohort.Similarly, the prevalence of underweight was higher (43.2%) among children of flooded affected areas compared to non-flooded areas (27.1%). Majority of children of same age group 30-41 months were severely underweight in both cohorts; 14.6% in flooded and 6.7% in non-flooded cohort. Only 23.1% of household from flood affected and 31.2% of non-flood affected were food secure. The flooding was most significantly associated with wasting in bivariate analysis (OR 1.815; 95% CI: 1.140, 2.88) but not significant in adjusted model (aOR 1.014; 95% CI: 0.62, 1.96). Dalit children (OR 1.811; 95% CI: 1.141, 2.874) and mother with more than two under five children presented a higher likelihood of wasting compared to its counterpart (OR 2.023; 95% CI: 0.684, 5.983). It was also found that children whose mothers did not wash their hand after child defecation discovered to have higher chance of being wasted than its counterpart OR 2.090; 95% CI: 1.039, 4.203). Similarly, children of mother's having more than two under five children were also more likely to be wasted compared (aOR 2.598; 95% CI: 0.606, 11.151) compared to reference group in multivariate analysis. In bivariate analysis, exposure to flood (OR 2.042; 95% CI: 1.32, 3.16),mother's education (OR 1.385; 95% CI: 0.385, 2.146), Diarrhoea (OR 1.598; 95% CI: 1.038, 2.460), ANC checkup (OR 1.585; 95% CI: 0.585, 3.077), childhood morbidity (OR 1.720; 95% CI: 1.050, 2.816) and after child defecation (OR 1.955; 95% CI: 1.133, 3.373)was statistically significant with underweight. After adjusting the confounders, again flooded exposure was strongly associated with underweight (aOR 1.780; 95% CI: 1.11, 2.85) in multivariate analysis. It was expected that the information from this study might be helpful for upcoming researcher as a baseline information for a similar research. Along with this, evidences might be used by the government and humanitarian organization to implement appropriate programs aimed to improving the nutritional status of flood affected children for particular areas.